Biomechanical analysis of active drag in swimming - Alcock, A.; Mason, B. (ISBS - Conference Proceedings Archive (Konstanz), 2007)
Active drag measurement through an entire swimming stroke was computed from the swimmer`s maximum sprint speed and the assistive force required to tow the swimmer at a slightly higher known velocity. The mean values of the active drag obtained were similar to those previously reported (Male 95 & 83 N, Female 73 & 69 N in freestyle and butterfly). A graph of time against active drag for butterfly highlighted the propulsion and recovery phases. The within stroke drag fluctuations in freestyle were less than in butterfly. The active drag graph combined with synchronised video would enable the swimmer`s technical efficiency to be evaluated throughout the stroke cycle. This method could be used to identify aspects of the swimmer`s stroke that corresponded with changes in the swimmer`s active drag.